Intertwining of localized (d) and delocalized (π) spins in magnetically frustrated two-dimensional metal-organic frameworks - Ugale, Ajay; Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Mandal, Rimpa; Singh, Kirandeep; Ballav, Nirmalya (Inorganic Chemistry, 2024)
Two-dimensional metal-organic frameworks (2D MOFs) are emerging as a new class of multifunctional materials for diversified applications, although magnetic properties have not been widely explored. The metal ions and organic ligands in some of the 2D MOFs are arranged in the well-known Kagome lattice, leading to geometric spin frustration. Hence, such systems could be the potential candidates to exhibit an exotic quantum spin liquid (QSL) state, as was observed in Cu-3(HHTP)(2) (HHTP = hexahydroxytriphenylene), with no magnetic transition down to 38 mK. Hereto, we have investigated the spin intertwining in a bimetallic 2D MOF system, M-3(HHTP)(2) (M = Cu/Zn)(,) arising from the localized (d-electron) and delocalized (pi-electron) S = 1/2 spins from the Cu(II) ions and the HHTP radicals, respectively. The origin of the spin frustration (down to 5K) was critically examined by varying the metal composition in bimetallic systems, CuxZn3-x(HHTP)(2) (x = 1, 1.5, 2), containing both S = 1/2 and S = 0 spins. Additionally, to gain a deeper understanding, we studied the spin interaction in the pristine Zn-3(HHTP)(2) system containing only S = 0 Zn(II) ions. In view of the quantitative estimate of the localized and delocalized spins, the d-pi spin correlation appears essential in understanding the unusual magnetic and/or other physical properties of such hybrid organic-inorganic 2D crystalline solids

Unconventional hole doping of S = ½ kagome antiferromagnet CoCu3(OH)6Cl2 - Mandal, Rimpa; Ninawe, Pranay; Ananthram, K. S.; Mhase, Akash; Gupta, Kriti; Saha, Sauvik; Ugale, Ajay; Singh, Kirandeep; Tarafder, Kartick; Ballav, Nirmalya (Advanced Physics Research, 2024)
Geometrically perfect S = ½ kagome lattices with frustrated magnetism are typically electrical insulators. Electron or hole doping is predicted to induce an exotic conducting state including superconductivity. Herein, an unconventional strategy of doping an S = ½ kagome lattice CoCu3(OH)6Cl2 is adopted – a structural analogue of a well-known quantum spin liquid (QSL) candidate herbertsmithite (ZnCu3(OH)6Cl2) – by integrating it with reduced graphene oxide (rGO) via in situ redox chemistry. Such an integration drastically enhances the electrical conductivity, resulting in the transformation of an insulator to a semiconductor, corroborating the respective density of states obtained from the density functional theory calculations. Estimation of the magnetic moments, data on the Hall-effect measurements, Bader charge analysis, and photoemission signals, altogether provide a bold signature of remote hole doping in CoCu3(OH)6Cl2 by rGO. The remote doping provides an alternative to the site doping approach to impart exotic electronic properties in spin liquid candidates, specifically, the generation of topological states like Dirac metal is envisioned.